2019
DOI: 10.1016/j.hemonc.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary persistence of hemoglobin F is protective against red cell sickling. A case report and brief review

Abstract: Fetal hemoglobin (HbF) is a physiologic protein tetramer that is crucial for a developing fetus to survive in utero. Maternal hemoglobin has a relatively lower affinity for oxygen, and thus allows for an efficient transfer of oxygen from maternal to fetal blood. In addition to fulfilling a critical physiologic role, HbF is also known to alleviate symptoms of sickle-cell disease (SCD). The concentration of HbF depends on several factors. HbF is elevated in inherited conditions, such as hereditary persistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
13
0
3
Order By: Relevance
“…However, the group with the HbSS genotype was more exposed to cesarean section than the other two. The protective effect of HbF and alpha-thal observed in our series, is similar to that reported by other authors in the associations S/β(0) thalassemia, S/β(+) thalassemia,21 or other major sickle cell syndromes like SC, SD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the group with the HbSS genotype was more exposed to cesarean section than the other two. The protective effect of HbF and alpha-thal observed in our series, is similar to that reported by other authors in the associations S/β(0) thalassemia, S/β(+) thalassemia,21 or other major sickle cell syndromes like SC, SD.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed a significant difference in weight gain in favor of the HbSS / PHHF and HbSS / alpha-thal genotypes. The observed difference could be associated with the protective effects of HbF21 and alpha-thal 22. From the hematological variables, the HbSS genotype has a high number of WBCs, reticulocytes, and platelets.…”
Section: Discussionmentioning
confidence: 96%
“…HbF'in %50 doygunluğa ulaştığ pO 2 değeri yaklaşık olarak 19 mmHg iken, HbA'nın ise 27 mmHg'dır. Bu özelliği nedeni ile HbF oksijenin anneden fötüse taşınmasını kolaylaştırdığı için intrauterin dönemin en önemli hemoglobinidir(2).Gestasyonel Yüksek HbF düzeyi -Uğur Kurtoğlu et al Genel Tıp Derg 2021;31(2)180-181…”
unclassified
“…Για το λόγο αυτό γίνεται προσπάθεια αύξησης των επιπέδων της HbF στους ασθενείς, η οποία έχει φανεί ότι ασκεί προστατευτική δράση έναντι της δρεπάνωσης των ερυθροκυττάρων. Πιο ειδικά, φαίνεται ότι η HbF (α2γ2) λόγω της παρουσίας των δυο γ-αλυσίδων, παρέχει υψηλότερη συγγένεια για το οξυγόνο απ' ό,τι η HbA ή η HbS αναστέλλοντας με αυτόν τον τρόπο τον πολυμερισμό της αποξυγονωμένης HbS και κατ'επέκταση τη δρεπάνωση των κυττάρων (Sokolova et al, 2017). Η πλέον ευρέως χρησιμοποιούμενη θεραπεία των ασθενών αυτών είναι η λήψη υδροξυουρίας (HU).…”
Section: δρεπανοκυτταρική αναιμίαunclassified
“…Το σύνδρομο της κληρονομικής παραμονής της εμβρυϊκής αιμοσφαιρίνης (Hereditary Persistence of Fetal Hemoglobin -HPFH syndrome) αποτελεί μια ασυμπτωματική κατάσταση κατά την οποία δεν συμβαίνει η δεύτερη μεταστροφή των σφαιρινών, με αποτέλεσμα η σύνθεση της HbF να μη σταματά μετά τη γέννηση, όπως συμβαίνει φυσιολογικά αλλά να συνεχίζει σε ποσοστό >2% και κατά την ενήλικο ζωή. Στο σύνδρομο αυτό τα επίπεδα της HbA2 συνήθως είναι μειωμένα ενώ τα ερυθροκύτταρα παρουσιάζουν μια φυσιολογική μορφολογία (Patrinos & Antonarakis, 2010, Sokolova et al, 2017. Τα HPFH σύνδρομα αποτελούν αντικείμενο μελέτης και έρευνας εδώ και αρκετές δεκαετίες, προκειμένου να διαλευκανθούν ο/οι μηχανισμοί που εμπλέκονται στη μεταστροφή των εμβρυϊκών αιμοσφαιρινών σε αυτές των ενηλίκων και κατ΄επέκταση η συνεχιζόμενη παραγωγή της HbF στο ενήλικο στάδιο.…”
Section: σύνδρομο κληρονομικής παραμονής της εμβρυϊκής αιμοσφαιρίνηςunclassified